Vibration Control of Structures - Fischer, Cyril, editor 650235; Náprstek, Jiří, editor‡ 650236 (London : Intechopen, 2023)
Structural vibration control is designed to suppress and control any unfavorable vibration due to dynamic forces that could alter the performance of the structure. Although many vibration control schemes have been investigated so far, additional questions involving their practical application remain to be studied. This book provides the reader with a comprehensive overview of the state of the art in vibration control and safety of structures, in the form of an easy-to-follow, article-based presentation that focuses on selected major developments in this critically important area.